Health Humanities for Quality of Care in Times of COVID -19 - Marini, Maria Giulia; McFarland, Jonathan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The Covid pandemic has led us into an upheaval that has made us question the certainties underlying what it means to be a human being in our age; the ability to control medical and social facts through evidence. For the first-time western and developed countries have had to confront what many populations from the developing world (Africa. Latin America, etc) face on a daily basis with HIV and Ebola, etc. The Interconnectedness of Globalization has been the real disseminating catalyst of COVID 19, and many scientists wonder if this virus is the result of the Anthropocene age, with its indisputable lack of respect for the natural ecosystems. The virus has demonstrated that our frailty is only skin deep, and it has not only brought death, despair, but it has broken our interdependency as human beings, by imposing self- isolation as well as creating new ways of connections so that safety cannot imply loneliness. In this book, the coping strategies that originate from the multiple languages of care such as narrative, literature, science, philosophy, art, digital science are shown not only as reflective tools to promote health but also wellbeing amongst carers, patients, students, and citizens of our planet Earth. These strategies should be supported by the decision makers since they are low-cost investments necessary to make the health care system work. They however require a change of cultural paradigm. This book is a useful toolkit for patients, citizens and care services physicians who want to learn more on how to live better with this new world. .
1 The COVID-19 pandemic: the possible scientific and layman narratives for its origin. The consequences of the pandemic on the human being according to the biological psychological social and existential model and to the biomedical model -- 2 The pandemy of lies, fakenews and misinformation during the COVID-19 crisis -- 3 Crossing the first wave of COVID -19: the engaging and disengaging factors for coping for speaking about burn out and the trauma of health care providers -- 4 The grief for the loss: The Impossibility of funeral rituals during the lock down, and the need to mourn the people died. The increase of mental illness condition due to the high psychological toll -- 5 The Consolation of the Written Word: Reading and Writing to Engage and Escape the Pandemic -- 6 The interplay between art and nature as factors for wellbeing -- 7 Spirituality as the basis and foundation of the medical profession for a holistic understanding of the human being as a bio-psycho-socio-spiritual entity -- 8 The long Covid-19: time for resilience for health care providers, citizens, students, patients, caregivers -- 9 Health care organization: roles and actors of the districts, of the community care, home care and of the hospital setting, bioethical decisions on quality and quantity of life -- 10 So far so near: telemedicine, teleconsulting, distant teaching and smart working in health care and social services -- 11 Towards a new respect for the ecosystem and the humans: advices for economy, industry, labour forces, schools and academies. .
Keywords: Medical care; Medicine and the humanities; Public health; Epidemiology; Bioethics; Health Care; Medical Humanities; Public Health; Epidemiology; Bioethics; COVID-19; Medical Care